The Effect Of Country-Of-Origin, Consumer Characteristics And Attitudes On Consumer Behaviour Towards Foreign Clothing Brands In Nairobi, Kenya - Ngugi Njuguna, James (British Journal of Marketing Studies, 2015)
The country-of-origin (COO) concept refers to the country where a particular product is made and is anchored on the international marketing theory. The broad objective of this pioneering study was to determine the effect of COO, consumer characteristics and attitudes on consumer behaviour towards foreign clothing brands in Nairobi, Kenya. The specific objectives were to: assess the influence of COO on consumer behaviour; determine the influence of country-of-origin on consumer attitudes; establish the influence of consumer attitudes on consumer behaviour; assess the influence of consumer characteristics on consumer behaviour; determine the extent to which consumer characteristics moderate the relationship between COO and consumer behaviour; assess the degree to which consumer attitudes influence the relationship between country-of-origin and consumer behaviour and; establish the extent to which the relationship between COO and consumer behaviour towards foreign clothing brands is influenced by consumer characteristics and by consumer attitudes. The pertinent hypotheses were derived from the objectives. The study adopted a descriptive cross-sectional research design which facilitated testing of hypotheses quantitatively and ensured that conclusions about the COO research problem were based on the information provided at the time of the research. Primary data were collected using semi-structured questionnaires from a study population comprising 384 consumers of clothing brands across Nairobi County, Kenya. Data were analyzed using descriptive statistics and inferential statistics. The results of the study established that country-of-origin influences consumer behaviour towards foreign clothing brands and there was a significant association among the two. The findings also revealed that consumer characteristics directly influence consumer behaviour and also moderate the relationship between COO and consumer behaviour. There was a significant relationship between consumer characteristics and consumer behaviour. Furthermore, the results showed that consumer attitudes strongly mediate the relationship between country-of-origin and consumer behaviour, and there was a significant association among the two. Finally, the joint effect of COO, consumer characteristics and consumer attitudes was greater than the individual effects of the independent, mediating and moderating variables on consumer behaviour towards foreign clothing brands. The combined effect of these variables on consumer behaviour was also found to be statistically significant. The study has made contribution to theory, policy and practice in relation to consumer behaviour towards foreign clothing brands in general and specific influence of country-of-origin, consumer attitudes and consumer characteristics. The selection of the study variables was not exhaustive. The use of a relatively small population, use of a descriptive cross-sectional research design and testing of COO as a single concept put constraints on the generalizability of the results. The use of quantitative methods alone is also restrictive. Future research should seek to address these limitations by inclusion of the additional factors; use of a longitudinal and broader research design and; incorporation of qualitative research techniques such as focus group sessions and structured interviews.